704 An Audit of Marking of Cutaneous Lesions in A Two-Week Wait Skin Malignancy Service. (12th October 2021) - Sutcliffe, A; Chang, C; Sugden, P
Abstract: Aim: Clinical photography enhances a medical record and facilitates communication with other professionals involved in care. It is utilised frequently in the management of skin malignancy. The essence of good photography lies in accurate identification of the cutaneous lesion in question. National guidelines and local policy advise the use of circumferential marking to delineate a lesion of interest, and an alphabetical system for marking of multiple lesions. We audited compliance to standards for medical illustrations of cutaneous lesions in the two-week wait skin cancer clinic at University Hospital North Durham. Method: Prospective audit of patients attending the clinic over a 7-day period (07/09/20-15/09/20). Data was collated from electronic records on a number of variables. Results: 175 patients met inclusion criteria. The majority (n = 160, 89.9%) were referred for a single lesion, the rest for multiple lesions. Hospital clinical photography was obtained in 148 patients (83.2%). Marking was deemed inappropriate in 44.6% of those in which clinical photography was obtained. Of these 66 cases, 12 cases were multiple lesions marked without letters, 52 had an incorrect indicator for the lesion (such as arrows or dots, allowing more ambiguous interpretation), and 8 had no indicator at all. Incidentally, one patient was photographed with dressings covering the lesions. Conclusions: Compliance with standards for demarcation of skin lesions for clinical photography was found to be poor. This permits the wrong identification of lesions in future treatment episodes and could potentially have a significant impact on care. We propose the introduction of a referral document illustrating correct marking guidelines.